Cancer Therapy–Related Cardiac Dysfunction and Heart Failure: Part 1. (January 2016) - Bloom, Michelle W.; Hamo, Carine E.; Cardinale, Daniela; Ky, Bonnie; Nohria, Anju; Baer, Lea; Skopicki, Hal; Lenihan, Daniel J.; Gheorghiade, Mihai; Lyon, Alexander R.; Butler, Javed
Abstract : Advances in cancer therapy have resulted in significant improvement in long-term survival for many types of cancer but have also resulted in untoward side effects associated with treatment. One such complication that has become increasingly recognized is the development of cardiomyopathy and heart failure. Whether a previously healthy person from a cardiovascular perspective develops cancer therapy–related cardiac dysfunction or a high-risk cardiovascular patient requires cancer therapy, the team of oncologists and cardiologists must be better equipped with an evidence-based approach to care for these patients across the spectrum. Although the toxicities associated with various cancer therapies are well recognized, limitations to our understanding of the appropriate course of action remain. In this first of a 2-part review, we discuss the epidemiologic, pathophysiologic, risk factors, and imaging aspects of cancer therapy–related cardiac dysfunction and heart failure. In a subsequent second part, we discuss the prevention and treatment aspects, concluding with a section on evidence gap and future directions. We focus on adult patients in all stages of cancer therapy from pretreatment surveillance, to ongoing therapy, and long-term follow-up.